Analysis of the overcapacity and overfishing pillar of the WTO fisheries subsidies negotiations - Peter Lunenborg (South Centre, 2020)
Sustainable Development Goal (SDG) 14.6 asks World Trade Organization (WTO) Members to “prohibit certain forms of fisheries subsidies which contribute to overcapacity and overfishing”. Hence, the pillar on overcapacity and overfishing (O&O) is the most important pillar of the fisheries subsidies negotiations. However, WTO Members have not yet agreed on the approach to prohibition. This research paper distinguishes three types of approaches: the fisheries management linked approach (sometimes referred to as effects-based approach), capping and list-based approach. This paper argues that the core of the prohibition in the Overfishing and Overcapacity pillar should be list-based and be applicable to large scale fisheries who receive the bulk of global fisheries subsidies especially those that are capacity-enhancing. For subsidies which are not prohibited an effects-based test might be considered. A supplementary subsidy prohibition covering areas beyond national jurisdiction (ABNJ) could be considered, or the vessels or operations targeted by proponents of the ABNJ proposals could be deemed `large scale'. If capping remains on the table, capping subsidies per fisher could be explored. Special and Differential Treatment should be an integral element of the outcome as developing countries whose fisheries sector are less developed should not take on the same commitments.
Keywords: 300; Fisheries Subsidies; Overcapacity and Overfishing (O&O); Special and Differential Treatment; Sustainable Development Goals (SDGs); World Trade Organization (WTO); WTO